South Asian older adults with memory impairment: improving assessment and access to dementia care. (12th December 2014) - Giebel, Clarissa M.; Zubair, Maria; Jolley, David; Bhui, Kamaldeep Singh; Purandare, Nitin; Worden, Angela; Challis, David
<x xml:space="preserve">Abstract</x> Objective With increasing international migration, mental health care of migrants and ethnic minorities is a public health priority. South Asian older adults experience difficulties in accessing services for memory impairment, dementia and mental illness. This review examines barriers and facilitators in the pathway to culturally appropriate mental health care. Methods Web of Knowledge, Pubmed and Ovid databases were searched for literature on South Asian older adults or their family carers, their understandings of mental illness and dementia and their pattern of service use. Dates were from 1984 to 2012. Abstracts were assessed for relevance, followed by detailed reading of salient papers. Three researchers rated the quality of each included study. A narrative synthesis was undertaken of extracted and charted data. Results Eighteen studies met the eligibility criteria for the review. South Asians and health professionals highlighted several difficulties which deterred help seeking and access to care: a lack of knowledge of dementia and mental illness, and of local services; stigma; culturally preferred coping strategies; and linguistic and cultural barriers in communication and decision making. Conclusions To improve access for these groups, service users and providers need to be better informed; services need to be more culturally tailored, sometimes employing staff with similar cultural backgrounds; and health professionals can benefit from dementia education and knowledge of local services. These factors are key to the delivery of the National Dementia Strategy in England. Copyright © 2014 John Wiley & Sons, Ltd.